2016
DOI: 10.1051/ctv/20163102051
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of some indigenousSaccharomyces cerevisiaeisolates obtained during vinification of ‘Kalecik Karasi’ and ‘EMIR’ grapes grown in Central Anatolia

Abstract: SUMMARYIn this research, 20 Saccharomyces cerevisiae isolates obtained during spontaneous fermentation of 'Kalecik Karasi' and 'Emir' grapes were evaluated for their technological characteristics. All of the S. cerevisiae isolates could grow at the tested temperatures, pH values and sugar concentration. Most of the tested isolates (80%) produced the same level of H 2 S than the control culture. All indigenous S. cerevisiae isolates showed similar carbon assimilation and fermentation profiles, with a few except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…). It has been reported that low molecular weight peptides, and especially amino acids, can be produced and may have direct involvement in forming fermentation bouquet, through their catabolism by the activity of these enzymes during fermentation (Senses‐Ergul and Ozbas ). Phosphatases catalyse the hydrolysis of C‐O‐P linkage of a wide variety of phosphate esters.…”
Section: Discussionmentioning
confidence: 99%
“…). It has been reported that low molecular weight peptides, and especially amino acids, can be produced and may have direct involvement in forming fermentation bouquet, through their catabolism by the activity of these enzymes during fermentation (Senses‐Ergul and Ozbas ). Phosphatases catalyse the hydrolysis of C‐O‐P linkage of a wide variety of phosphate esters.…”
Section: Discussionmentioning
confidence: 99%
“…Region-specific populations called as "microbial fingerprint" vary over time and have their own dynamics related to the regional factors (González-Alonso et al, 2021). These indigenous yeasts are considered more competitive than commercial yeasts as they are presumed to possess better adaptation to the ecological and technological conditions specific to their regions (Senses-Ergul and Ozbas, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous microbial strains are able to adapt more to ecological and technological conditions of their own environment and their dominating ability during the fermentation process can help preserve important quality of the final products (Senses‐Ergul & Ozbas, ).Several researchers have previously reported the beneficial roles of autochthonous LAB and yeasts in some fermented foods (Di Cagno et al , ; Senses‐Ergul & Ozbas, ; Palla et al , ). Di Cagno et al () mentioned that mixed starter of autochthonous LAB was able to preserve the texture, colour, sensory and shelf life quality of fermented red and yellow peppers.…”
Section: Introductionmentioning
confidence: 99%